Comparative study of electrical stimulation of the heart with VDD and DDD pacemakers as to the evolution to atrial fibrillation - de Campos, Nelson Leonardo Kerdahi Leite [UNESP]; de Andrade, Rubens Ramos [UNESP]; Fellicio, Marcello Laneza [UNESP]; Martins, Antônio Sergio [UNESP]; Garzesi, André Monti [UNESP]; Garcia, Leonardo Rufino [UNESP]; Takeda, Tassya Bueno [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2017)
Introduction: The pacemaker implantation VDD is considered simpler, faster, less expensive and causes fewer complications compared to DDD. However, the VDD pacemaker has not been widely used in many centers, perhaps for fear of dysfunction of the sinus node and the reduction of atrial sensitivity by the pacemaker during follow-up after implantation. Objective: To compare patients with DDD and VDD pacemakers regarding the evolution of chronic atrial fibrillation (AF) and length of stay outside this postoperative arrhythmia. Methods: It was included 158 patients with dual chamber pacemakers, 48 DDD and 110 VDD. Follow-up period: between January 1, 1999 and December 31, 2015. The mean follow-up of patients with DDD was 5.35 years and the VDD, 4.74 years. The percentage of each group (DDD and VDD) which evolved to AF during follow-up was assessed. Also, it was made an actuarial study with the respective curves indicating the time free from AF for each group. Patients were classified according to the diagnosis that led to pacemaker implantation and the degree of heart failure. Results: The percentage of patients who developed AF was higher in DDD group (10.42%) than in VDD group (6.36%), but without statistical significance. Patients with DDD and VDD remained free of AF for similar period. Conclusion: Considering the results, the VDD pacemaker continues to be a good option to the DDD for routine use in cases properly indicated.
Keywords: Artificial; Atrial fibrillation; Atrioventricular block; Pacemaker